1982
DOI: 10.1044/jshd.4702.210
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Language Tasks for Identifying Senile Dementia

Abstract: More than two million elderly Americans suffer from senile dementia, an age-related disease affecting memory, intellect, and communication. The purpose of this study was to explore the diagnostic efficacy of language tasks for identifying senile dementia. The performance of 35 dementia patients was compared to that of 28 normal senescents on five language tasks and certain psychological measures reputed to be sensitive to the disease such as the Block Design and Similarities subtests of the Wechsler Adult Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2
5

Year Published

1984
1984
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 0 publications
2
44
2
5
Order By: Relevance
“…Test results for normal subjects have been published for the Boston Naming Test (Van Gorp et al, 1986), Word Fluency (animals, towns and phonemic fluency) (Hart et al, 1988) and Story Retelling (immediate and delayed) (Bayles and Boone, 1982). Van Gorp (1986) reported that his subjects were of relatively high educational status, which suggests comparability with our patient group.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Test results for normal subjects have been published for the Boston Naming Test (Van Gorp et al, 1986), Word Fluency (animals, towns and phonemic fluency) (Hart et al, 1988) and Story Retelling (immediate and delayed) (Bayles and Boone, 1982). Van Gorp (1986) reported that his subjects were of relatively high educational status, which suggests comparability with our patient group.…”
Section: Discussionmentioning
confidence: 87%
“…Published work reports comparisons of various combinations of these clinical groups, AD, VaD, depressed and normal elderly (Bayles and Boone, 1982;Hier et al, 1985;Emery and Breslau, 1989) Both dementia groups in this study have mean scores on the MMSE and CAMCOG indicating mild impairment. All dementia patients had NART scores of above average, indicating a high degree of intellectual ability.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bayles and Boone (1982) found that a task requiring subjects to identify semantic errors in spoken sentences was the most discriminating of five language tasks in distinguishing dementia subjects from normally ageing individuals. Emery and Emery (1 984) reported dementia subjects demonstrating a hierarchical performance across several language tasks.…”
Section: Expressive Language Characteristics In Probable Alzheimer's mentioning
confidence: 99%
“…Recent findings suggest that communication difficulties exist at all stages of dementia (Bayles 1986, Bayles and Boone 1982, Obler and Albert 1981. However, the most prominent difficulties involve the semantic component of language while syntax and phonology remain relatively intact, at least until the severe stages of the disease (Appell et al 1982, Bayles and Boone 1982, Hier et al 1985.…”
Section: Introductionmentioning
confidence: 98%